2017
DOI: 10.1016/j.ecolecon.2016.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Bloom and bust: Toxic algae's impact on nearby property values

Abstract: Over the past decade harmful algal blooms (HABs) have become a nationwide environmental concern. HABs are likely to increase in frequency and intensity due to rising summer temperatures caused by climate change and higher nutrient enrichment from increased urbanization. Policymakers need information on the economic costs of HABs to design optimal management policies in the face of limited budgets. Using a detailed, multilake hedonic analysis across 6 Ohio counties between 2009 and 2015 we show capitalization l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 28 publications
4
43
0
Order By: Relevance
“…This result is consistent with Dornbusch and Barrager [], Netusil et al . [], and Wolf and Klaiber [], which found that water quality could affect the value of nonwaterfront properties up to 1 mi from the waterbody. Our results suggest that water quality likely has no significant effect on properties a mile or more from the shoreline.…”
Section: Estimation Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This result is consistent with Dornbusch and Barrager [], Netusil et al . [], and Wolf and Klaiber [], which found that water quality could affect the value of nonwaterfront properties up to 1 mi from the waterbody. Our results suggest that water quality likely has no significant effect on properties a mile or more from the shoreline.…”
Section: Estimation Resultsmentioning
confidence: 99%
“…In order to determine the specific distance where the effect drops off, we use 22 dummy distance dummy variables at 100 m intervals (0–100, 100–200, 200–300 m, …, 2000–2100, and greater than 2100 m). Then, we run our model and our results suggest that the distance water quality interactions become insignificant above 1000 m and the distance impacts become insignificant above 1500 m. To be conservative, we chose 1500 m as the bench mark which is also consistent with the hedonic literature [ Netusil et al ., ; Wolf and Klaiber , ]. We use distinct distance categories because it has the advantage of capturing nonlinear effects unlike a continuous distance variable.…”
Section: Hedonic Model Estimationmentioning
confidence: 99%
See 2 more Smart Citations
“…Wolf and Klaiber (2017) reported the negative impact of these blooms on house values for six counties surrounding four Ohio lakes [55]. The data comprised property sales of single family homes between July 2009 and April 2015.…”
Section: Recent Us Studies: 2003-2017mentioning
confidence: 99%